The Midlife Women's Health Study - a study protocol of a longitudinal prospective study on predictors of menopausal hot flashes - Ayelet Ziv-Gal; Rebecca L. Smith; Lisa Gallicchio; Susan R. Miller; Howard A. Zacur; Jodi A. Flaws (BMC, 2017)
Abstract Background The Midlife Women's Health Study (MWHS) was developed to address some of the gaps in knowledge regarding risk factors for hot flashes among generally healthy midlife women during their menopausal transition. This manuscript describes the methods from the study and the main findings that were published to date, with a focus on predictors of hot flashes. This study was initially funded to test the hypothesis that obesity is associated with an increased risk of hot flashes through mechanisms that involve ovarian failure, altered sex steroid hormone levels, and selected genetic polymorphisms. Methods/Design The MWHS was conducted between 2006 and 2015 as a prospective longitudinal population-based study of generally healthy midlife women (ages 45 to 54 years) during their natural menopausal transition. Women were eligible if they had intact uteri and both ovaries and reported having at least 3 menstrual periods in the last 12 months. Exclusion criteria included pregnancy, cancer, and use of hormonal/hormone-like supplements. Overall, 780 women were recruited into the study. The majority of study participants were followed for 4 to 7 years. At annual visits, women donated blood and urine samples, completed questionnaires, had a vaginal ultrasound, and had their anthropometric measurements taken. Discussion Several risk factors for menopausal hot flashes were identified or confirmed, including older age, perimenopausal status, current and former cigarette smoking, lower estradiol levels, lower progesterone levels, black race, and depressive symptoms. Factors that were associated with decreased odds of hot flashes included moderate alcohol consumption and more than 5 years of cessation of cigarette smoking. Body mass index was not associated with hot flashes. The MWHS has provided important information regarding hot flashes. The study methods are rigorous and can be easily adopted by research groups investigating naturally occurring menopausal hot flashes.